Microbial methane formation in deep aquifers of a coal-bearing sedimentary basin, Germany - Gründger, Friederike; Jiménez, Núria; Thielemann, Thomas; Straaten, Nontje; Lüders, Tillmann; Richnow, Hans-Hermann; Krüger, Martin (Frontiers in Microbiology, 2015)
Coal-bearing sediments are major reservoirs of organic matter potentially available for methanogenic subsurface microbial communities. In this study the specific microbial community inside lignite-bearing sedimentary basin in Germany and its contribution to methanogenic hydrocarbon degradation processes was investigated. The stable isotope signature of methane measured in groundwater and coal-rich sediment samples indicated methanogenic activity. Analysis of 16S rRNA gene sequences showed the presence of methanogenic Archaea, predominantly belonging to the orders Methanosarcinales and Methanomicrobiales, capable of acetoclastic or hydrogenotrophic methanogenesis. Furthermore, we identified fermenting, sulfate-, nitrate-, and metal-reducing, or acetogenic Bacteria clustering within the phyla Proteobacteria, complemented by members of the classes Actinobacteria, and Clostridia. The indigenous microbial communities found in the groundwater as well as in the coal-rich sediments are able to degrade coal-derived organic components and to produce methane as the final product. Lignite-bearing sediments may be an important nutrient and energy source influencing larger compartments via groundwater transport.